SUL CONCETTO DI VOLTO NEL FIGLIO DI DIO DI ROMEO CASTELLUCCI: TRA PIETÀ E DISGUSTO - Maddalena Mazzocut-Mis , Maddalena (ΠΑΡΑΒΑΣΙΣ/PARABASIS, 2025)
Romeo Castellucci is a renowned director, set designer, and playwright from Italy, considered one of the most influential and innovative artists in the field of contemporary theater. He is known for pushing the boundaries of contemporary theater and creating thought-provoking works that challenge audiences to engage with complex and uncomfortable themes. His exploration of disgust as an aesthetic category is just one example of his innovative and influential approach to theater. The work Sul concetto di volto nel Figlio di Dio is known for its impact on the spectator’s experience. In this play, Castellucci portrays life in its raw and extreme form, which can evoke strong feelings of anxiety and disgust in the audience. The play represents the physiological aspects of humanity that are often considered unpleasant or repulsive. It challenges traditional notions of elevation and salvation by juxtaposing the image of Christ’s face with the portrayal of bodily functions, like the loss of control over bowel movements in an elderly person. This contrasting imagery of Christ’s distant and hieratic face being struck by the same fecal substance can be seen as a metaphorical statement about the vulnerability of the human condition, despite any perceived divinity or elevated status.